LIPOXYGENASE INHIBITORY ASSAY OF ETHYL ACETATE FRACTION FROM STAR FRUIT LEAVES (AVERRHOA CARAMBOLA L.) FROM THREE REGIONS IN WEST JAVA - SUBARDINI, DEFI SUCIANA; ELYA, BERNA; NOVIANI, ARIKADIA (International Journal of Applied Pharmaceutics, 2020)
Objective: Averrhoa carambola L. leaves have been used as a traditional medicine. The study aimed to examine the anti-inflammatory activity of A. carambola L. plant extracts using a lipoxygenase inhibition assay based on ethyl acetate fractions of A. carambola L. leaves obtained from three regions in West Java. Methods: Extracts from A. carambola L. leaves were obtained by maceration method using 70% ethanol followed by fractionation using liquid-liquid partitioning until the ethyl acetate fraction was obtained. Subsequently, lipoxygenase inhibition activity of the ethyl acetate fraction was tested using linoleate acid as the substrate, and the total flavonoid and total phenol contents were determined. The correlation between the IC50 values and the total flavonoid and total phenol contents obtained from the ethyl acetate fraction were analyzed. Results: The ethyl acetate fraction from the sample inhibited lipoxygenase enzyme activity with IC50 values of 19.38, 16.65, and 15.07 μg/mL, respectively. The total flavonoid contents in the ethyl acetate fractions obtained from Depok, Subang, and Sukabumi regions were 14.88, 16.88, and 22.27 mg QE/g of sample, respectively, whereas the total phenol contents were 54.10, 61.06, and 72.18 mg gallic acid equivalents/g of sample, respectively. Conclusion: There was a high correlation between the IC50 values and the total flavonoid and total phenol contents, with correlations coefficients of −0.917 and −0.960, respectively, which indicated that the higher the total flavonoid and total phenol contents, the lower the IC50 values.